Decade of difference - Houston, Joel, PhD, author.
1 online resource.
Keywords: "When approaching the most public disagreement over predestination in the eighteenth century, the 'Free Grace' controversy between John Wesley and George Whitefield, the tendency can be to simply review the event as a row over the same old issues. This assumption pervades much of the scholarly literature that deals with early Methodism. Moreover, much of that same literature addresses the dispute from John Wesley's vantage point, often harbouring a bias towards his Evangelical Arminianism. Yet the question must be asked: was there more to the 'Free Grace' controversy than a simple rehashing of old arguments? This book answers this complex question by setting out the definitive account of the 'Free Grace' controversy in first decade of the Evangelical Revival (1739-49). Centred around the key players in the fracas, John Wesley and George Whitefield, it is a close analysis of the way in which the doctrine of predestination was instrumental in differentiating the early Methodist societies from one another. It recounts the controversy through the lens of doctrinal analysis and from two distinct perspectives: the propositional content of a given doctrine and how that doctrine exerts formative pressure upon the assenting individual(s). What emerges from this study is a clearer picture of the formative years of early Methodism and the vital role that doctrinal pronouncement played in giving a shape to early Methodist identity. It will, therefore, be of great interest to scholars of Methodism, Evangelicalism, Theology and Church History"--